Implementation of total productive maintenance in pt. Ip lontar - Sidabutar, Daniel; F.Firman, Aries (The Indonesian Journal of Business Administration, 2019)
Abstract. Total Productive Maintenance (TPM) is a maintenance program which concentrates on total involvement of everyone from top management to all employees in the organization. TPM practice a maintenance program by doing training, Autonomous Maintenance and 5S (Sort, Set in order, Shine, Standardize, Sustain). This program expect to the result in maximum Overall Equipment Effectiveness (OEE), tidier, neat, clean work place and morally boosted employees. This research was compiled based on qualitative methods by conducting interviews with top management, middle management in the company and customer. In-depth interviews were conducted to explore how the opinions of respondents regarding the implementation of total productive maintenance. From the results of interviews and literature studies, There are four recommendation that propose to PT IP Lontar for successful of TPM Implementation. Establish TPM Implementation team, OEE of equipment become employees KPI, Communication and promotion about TPM activity, and People development. In the end, if total productive maintenance has been implemented effectively, the company can reduce cost of maintenance and improve reliability of each equipment because it has a strong foundation in the form of structured maintenance system.Keywords: derating, total productive maintenance, employee involvement, OEE